2021
DOI: 10.3389/fmed.2021.670643
|View full text |Cite
|
Sign up to set email alerts
|

USA: Ophthalmologic Evaluation and Management of Acute Stevens-Johnson Syndrome

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) can cause significant damage to the ocular surface and eyelids. The sloughing and inflammation of the ocular mucosal epithelium during the acute phase may lead to scarring sequelae of the eyelids and ocular surface, resulting in pain and vision loss. Amniotic membrane transplantation (AMT) to the eyes and eyelids during the initial 1–2 weeks of the disease can decrease the chronic sequelae. The main development in the ophthalmologic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…More recently, a randomised controlled trial in 2016 found a significant benefit ( p = 0.042) at 6‐month follow‐up to the average best‐corrected visual acuity of the 25 eyes that received AMT and medical therapy over the 25 eyes that received medical therapy alone 29 . A 2021 review from the USA noted the growing literature supportive of early AMT in severe ocular SJS/TEN, particularly if carried out in the first week of disease 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a randomised controlled trial in 2016 found a significant benefit ( p = 0.042) at 6‐month follow‐up to the average best‐corrected visual acuity of the 25 eyes that received AMT and medical therapy over the 25 eyes that received medical therapy alone 29 . A 2021 review from the USA noted the growing literature supportive of early AMT in severe ocular SJS/TEN, particularly if carried out in the first week of disease 30 …”
Section: Discussionmentioning
confidence: 99%
“…29 A 2021 review from the USA noted the growing literature supportive of early AMT in severe ocular SJS/TEN, particularly if carried out in the first week of disease. 30 Anogenital care…”
Section: Ocular Carementioning
confidence: 99%
“…Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) can cause severe scarring of the ocular surface, dry eye and visual impairment [ 1 ]. The use of amniotic membranes (AM) in the acute phase of SJS/TEN can minimize the development of late complications [ 2 ].…”
Section: Introductionmentioning
confidence: 99%